Interlayer toughening effect of graphene oxide and polydopamine modified kevlar fiber on the carbon fiber panel/plastic honeycomb sandwich structure - Zhaoqi Yang; Jicai Liang; Haotian Zheng; Ce Liang (Journal of Materials Research and Technology)
This study examines the performance of modified Kevlar fiber-reinforced carbon fiber/plastic honeycomb panels. Graphene oxide (GO) is successfully grafted onto the Kevlar fiber surface using polydopamine (PDA) as a binding medium. The combined effect of GO and PDA's secondary functionalization significantly improves bonding strength. The toughened samples exhibit markedly higher peak force and energy absorption compared to the untoughened ones. Specifically, the PDA-GO-2 toughened specimen shows the best performance, with peak force and energy absorption increased by 70.9% and 109.4%, respectively. Kevlar fibers and resin form a complex ''compound and rounded structure'' at the edge of the honeycomb core. This structure enhances the bonding strength between the carbon fiber-reinforced polymer (CFRP) panel and the polypropylene (PP) honeycomb core. Furthermore, the PDA and GO treatment improves the fibers' wettability, tensile strength, surface roughness, and specific surface area, facilitating better mechanical interlocking between the fiber and resin. GO enhances the contact between epoxy resin and fibers by facilitating covalent and hydrogen bond interactions, resulting in a tighter transition interface that improves the interfacial adhesion strength between the fibers and the resin.